135Xe measurements with a two-element CZT-based radioxenon detector for nuclear explosion monitoring. (April 2017) - Ranjbar, Lily; Farsoni, Abi T.; Becker, Eric M.
Abstract: Measurement of elevated concentrations of xenon radioisotopes ( 131m Xe, 133m Xe, 133 Xe and 135 Xe) in the atmosphere has been shown to be a very powerful method for verifying whether or not a detected explosion is nuclear in nature. These isotopes are among the few with enough mobility and with half-lives long enough to make their detection at long distances realistic. Existing radioxenon detection systems used by the Comprehensive Nuclear-Test-Ban Treaty Organization (CTBTO) suffer from problems such as complexity, need for high maintenance and memory effect. To study the response of CdZnTe (CZT) detectors to xenon radioisotopes and investigate whether it is capable of mitigating the aforementioned issues with the current radioxenon detection systems, a prototype detector utilizing two coplanar CZT detectors was built and tested at Oregon State University. The detection system measures xenon radioisotopes through beta-gamma coincidence technique by detecting coincidence events between the two detectors. In this paper, we introduce the detector design and report our measurement results with radioactive lab sources and 135 Xe produced in the OSU TRIGA reactor. Minimum Detectable Concentration (MDC) for 135 Xe was calculated to be 1.47 ± 0.05 mBq/m 3 . Highlights: A new radioxenon detection system was designed and built using CdZnTe detectors. The energy resolution of 250 keV from 135 Xe was measured to be 4.4% FWHM. Substantial energy resolution improvement compared to other β-γ coincidence systems. Minimum Detectable Concentration (MDC) of 135 Xe for this system is 1.47 ± 0.05 mBq/m 3 . A 6-CZT design will have MDC of less than 1 mBq/m 3 for 135 Xe (0.09 ± 0.05 mBq/m 3 ).